Short-duration hypothermia completed prior to reperfusion prevents intracranial pressure elevation following ischaemic stroke in rats - Daniel Omileke (Nature Portfolio, 2021)
Abstract Reperfusion therapies re-establish blood flow after arterial occlusion and improve outcome for ischaemic stroke patients. Intracranial pressure (ICP) elevation occurs 18–24 h after experimental stroke. This elevation is prevented by short-duration hypothermia spanning the time of reperfusion. We aimed to determine whether hypothermia-rewarming completed prior to reperfusion, also prevents ICP elevation 24 h post-stroke. Transient middle cerebral artery occlusion was performed on male outbred Wistar rats. Sixty-minute hypothermia to 33 °C, followed by rewarming was induced prior to reperfusion in one group, and after reperfusion in another group. Normothermia controls received identical anaesthesia protocols. ΔICP from pre-stroke to 24 h post-stroke was measured, and infarct volumes were calculated. Rewarming pre-reperfusion prevented ICP elevation (ΔICP = 0.3 ± 3.9 mmHg vs. normothermia ΔICP = 5.2 ± 2.1 mmHg, p = 0.02) and reduced infarct volume (pre-reperfusion = 78.6 ± 23.7 mm3 vs. normothermia = 125.1 ± 44.3 mm3, p = 0.04) 24 h post-stroke. There were no significant differences in ΔICP or infarct volumes between hypothermia groups rewarmed pre- or post-reperfusion. Hypothermia during reperfusion is not necessary for prevention of ICP rise or infarct volume reduction. Short-duration hypothermia may be an applicable early treatment strategy for stroke patients prior to- during-, and after reperfusion therapy.